Tailoring the topography, crystalline structure, and piezoelectric response of electrospun biodegradable poly(3-hydroxybutyrate) scaffolds by glycine loading; Advanced Composites and Hybrid Materials; Vol. 8, iss. 6 - Shlapakova L. E. Lada Evgenievna; Shvartsman V. V. Vladimir; Slautin B. N. Boris; Lupascu D. C. Doru; Grubova I. Yu. Irina Yurievna; Sun Yi-Yang; Botvin V. V. Vladimir Viktorovich; Mathur S. Sanjay; Surmenev R. A. Roman Anatolievich; Surmeneva M. A. Maria Alexandrovna (2025, 2025)
Title screen